Prenova potoka Cheonggye v Seulu - Križnik, Blaž (Družboslovne razprave, 2007)
The article explores the broader social background of transformations that public space is undergoing amidst the conditions of transnational co-operationand growing competition among cities. The character of public space in global cities is becoming more homogenous and excluding due to its increasingly instrumental role in city development. The importance of public space for the formation of a democratic and heterogeneous civil society is thereby being eroded. We try to show how the recent restoration of the Cheonggye stream in Seoul in South Korea has influenced its social role and thus verify our assumption of the excluding nature of public space in global cities. In the conclusion we sum up the reasons why Cheonggyecheon is losing its past role of a place where civic society and local cultures were reproduced.
Keywords: Globalisation; Globalizacija; globalization; Mesta; Towns; Public spaces; Javne površine; Civil society; Civilna družba; Družbeni vidik; Social aspects; South Korea; Južna Koreja; javni prostor; Seul